2002
DOI: 10.4310/jdg/1090426286
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Behaviour of Tame Nilpotent Harmonic Bundles with Trivial Parabolic Structure

Abstract: Let E be a holomorphic vector bundle. Let θ be a Higgs field, that is a holomorphic section of End(E) ⊗ Ω 1,0 X satisfying θ 2 = 0. Let h be a pluriharmonic metric of the Higgs bundle (E, θ). The tuple (E, θ, h) is called a harmonic bundle.Let X be a complex manifold, and D be a normal crossing divisor of X. In this paper, we study the harmonic bundle (E, θ, h) over X − D. We regard D as the singularity of (E, θ, h), and we are particularly interested in the asymptotic behaviour of the harmonic bundle around D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…After a finite base change, we assume that the local monodromies are unipotent. By the result of Jost-Zuo [21], there exists a harmonic metric on the flat bundle W with finite energy which makes W into a Higgs bundle (F, η) on S. T. Mochizuki [25] has further analyzed the singularity of this harmonic metric and in particular shown that (F, η) admits a logarithmic extension (F , η) with logarithmic poles of Higgs field along D. By the uniqueness of such harmonic metrics, the induced metric n W coincides with the Hodge metric given by the C-PVHS V.…”
Section: Zariski Density Of Monodromy Groupmentioning
confidence: 99%
“…After a finite base change, we assume that the local monodromies are unipotent. By the result of Jost-Zuo [21], there exists a harmonic metric on the flat bundle W with finite energy which makes W into a Higgs bundle (F, η) on S. T. Mochizuki [25] has further analyzed the singularity of this harmonic metric and in particular shown that (F, η) admits a logarithmic extension (F , η) with logarithmic poles of Higgs field along D. By the uniqueness of such harmonic metrics, the induced metric n W coincides with the Hodge metric given by the C-PVHS V.…”
Section: Zariski Density Of Monodromy Groupmentioning
confidence: 99%
“…In order to simplify the discussion, we assume that X is the complement of a normal crossing divisor in a smooth projective vari-etyX. Along the divisor, we choose for the metric on X the product of hyperbolic metrics on the pointed disk D * and euclidean metrics on the disk D; see for instance [Moc02], subsection 4.1. This metric satisfies of course Assumption 1.…”
Section: On the Non-compact Casementioning
confidence: 99%
“…It would be good to have the full middle-convolution theory for the general setup of parabolic logarithmic λ-connections [110] [111] [112] [125]. This raises some nontrivial questions such as defining the middle higher direct image in the parabolic setting, obtaining a base-change result analogous to Convention 5.3, and showing polystability of the middle convolution.…”
Section: Further Questionsmentioning
confidence: 99%